Distribution of the AMPD1 C34T polymorphism in Polish power-oriented athletes - Cieszczyk, P.; Ostanek, M.; Leonska-Duniec, A.; Sawczuk, M.; Maciejewska, A.; Eider, J.; Ficek, K.; Sygit, K.; Kotarska, K. (Journal of Sports Sciences, 2011)
The aims of this study were to determine the distribution of the AMPD1 genotype among groups of high-level Polish power-oriented athletes, and to investigate potential associations between genetic polymorphism in exon 2 of the AMPD1 gene and power-oriented athlete status. Altogether, 158 male Polish power-oriented athletes were genotyped by PCR-RFLP. The genetic control group comprised 160 unrelated male volunteers. We observed significant differences in genotype distribution when all 158 athletes (89.25% CC, 10.75% CT, 0.00% TT; P = 0.0025) were compared with controls (75.00% CC, 23.75% CT, 1.25% TT). A significant deficiency of the T allele was noted in all subgroups (short-distance runners: 5.21%, P = 0.032; short-distance swimmers: 5.56%, P = 0.031; weightlifters: 5.36%, P = 0.024) compared with controls (13.13%), while this trend was even stronger when the frequency of the T allele was compared between controls and all 158 athletes (5.38%, P = 0.0007). Our results indicate a lower frequency of the AMPD1 exon 2 T34 allele in elite Polish power-oriented athletes. Our data suggest that the C allele may help athletes to attain elite status in power-oriented sports.